EMPIRIC DEMOCRACY AND THE REFERENCE OF POLITICAL PARTIES IN SINGLE CANDIDATE ELECTIONS - Sulistyowati Sulistyowati (UNISSULA, 2021)
The dynamic changes in the Law on Election for Governors, Regents, and Mayors prove that there are dynamics and progressiveness in the implementation of Pilkada. The process of the birth of laws, including the process of the birth of amendments to the Law, is a legal political process. The legal political process is under the authority of the legislator. The approach method used is normative juridical method. The power of legislators in the political and legal process is not absolute, because the government also has a domain of authority, although not as big as the authority of legislators. The result states that The legal political process always rests on the principle of normative democracy as the embodiment of the das sollen principle. At the level of implementation of the rule of law, there will always be legal anomalies, because there is a mismatch between normative democracy as the embodiment of the basic principle with empirical democracy as the embodiment of the basic sein principle. The legitimacy of a single candidate in Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors makes the preferences of political parties increasingly pragmatism.